PENGARUH KEPERCAYAAN MEREK TERHADAP KEPUTUSAN PEMBELIAN PAKET DATA TELKOMSEL PADA MASYARAKAT KELURAHAN BABURA SUNGGAL KECAMATAN MEDAN SUNGGAL MEDAN - Sagala, Roslinda; Sitanggang, Darna; Sitompul, Pandapotan (UNIKA Santo Thomas, 2024)
This research aims to explore the impact of variables such as brand predictability, brand preference, brand competence, brand reputation, and company trust on purchasing decisions. The research sample involves 96 respondents, and data collection utilizes questionnaires and interviews, with data analysis employing multiple linear regression techniques. The study results reveal that the variables of brand predictability (Pm), brand preference (Kpm), brand competence (Km), brand reputation (Rm), and company trust (Kp) positively influence purchasing decisions. Both the F-test and t-test indicate that each variable has a positive and significant impact, both partially and simultaneously, on purchasing decisions. The correlation coefficient (r) of 0.688 suggests a strong relationship among brand predictability, brand preference, brand competence, brand reputation, and company trust with purchasing decisions. Meanwhile, the coefficient of determination (R Square) of 0.444 indicates that 44.4% of the variation in purchasing decisions can be explained by these variables, while 55.6% is influenced by other unexamined factors. It is advisable to consider expanding the research sample by involving more respondents from the same neighborhood or other neighborhoods in similar regions. Expanding the scope of the study can provide a more comprehensive understanding of the impact of brand trust on purchasing decisions in diverse community contexts.